2010
DOI: 10.1371/journal.pgen.1001140
|View full text |Cite
|
Sign up to set email alerts
|

dMyc Functions Downstream of Yorkie to Promote the Supercompetitive Behavior of Hippo Pathway Mutant Cells

Abstract: Genetic analyses in Drosophila epithelia have suggested that the phenomenon of “cell competition” could participate in organ homeostasis. It has been speculated that competition between different cell populations within a growing organ might play a role as either tumor promoter or tumor suppressor, depending on the cellular context. The evolutionarily conserved Hippo (Hpo) signaling pathway regulates organ size and prevents hyperplastic disease from flies to humans by restricting the activity of the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
162
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(172 citation statements)
references
References 60 publications
9
162
1
Order By: Relevance
“…Elevation of Yki levels is sufficient to protect M +/− cells from cell competition and can even transform normal cells into supercompetitors (22,24,25). Remarkably, ex-lacZ, which was up-regulated in noncompeted scrib − clones, was not induced in scrib − clones surrounded by wild-type cells in most regions of eye and wing discs (Figs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Elevation of Yki levels is sufficient to protect M +/− cells from cell competition and can even transform normal cells into supercompetitors (22,24,25). Remarkably, ex-lacZ, which was up-regulated in noncompeted scrib − clones, was not induced in scrib − clones surrounded by wild-type cells in most regions of eye and wing discs (Figs.…”
Section: Resultsmentioning
confidence: 98%
“…Importantly, elevated levels of Yki can rescue M +/− cells from being eliminated by cell competition and also can transform normal cells into supercompetitors that induce apoptosis in their neighbors and proliferate at their neighbors' expense (22,24,25). Yki may increase the competitiveness of cells by inducing the expression of Myc, a known regulator of cell competition (24)(25)(26)(27). However, the reports that scrib − cells have high levels of Yki activity and the hypothesis that scrib − cells are eliminated by cell competition present a paradox.…”
mentioning
confidence: 99%
“…We also provided evidence that tissue damage may regulate dMyc expression at a post-transcriptional level. Two recent studies suggest that Yki-Sd may directly regulate dMyc transcription in wing imaginal discs [33,34]. We identified a 1 kb dMyc enhancer (dMyc1.0) that contains multiple consensus Sdand Stat-binding sites and is capable of mediating the transcriptional regulation of a reporter gene (dMyc1.0-luc) by Yki-Sd and Stat in S2 cells.…”
Section: Discussionmentioning
confidence: 96%
“…The Hippo pathway also inhibits expression of a microRNA bantam to affect organ size, although the downstream effector of bantam is not clear. Furthermore, Yki-Sd was shown to transcriptionally induce dMyc, a potent promoter of ribosome biogenesis and cell growth (Neto-Silva et al, 2010;Ziosi et al, 2010), which may mediate the cell competition phenomenon observed in tissues with imbalance of Hippo pathway activity. In addition, Yki induces E2F1 (Goulev et al, 2008), which may be involved in cell-autonomous regulation of cell proliferation; the EGFR ligands Vein, Keren, and Spitz (Zhang et al, 2009b;Ren et al, 2010); the Jak/Stat pathway ligands Unpaired1/2/3 (Upd1/2/3) (Karpowicz et al, 2010;Ren et al, 2010;Shaw et al, 2010;Staley and Irvine, 2010), which could mediate non-cell-autonomous function of the Hippo pathway; and the Hippo pathway genes Ex, Kibra, Crb, and Fj (Cho et al, 2006;Hamaratoglu et al, 2006;Genevet et al, 2009;Genevet et al, 2010), which may constitute a signal feedback loop.…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%